IMPLEMENTATION OF TOLERANCE EDUCATION ON TUMBANG KALANG VILLAGE FOR PEACE BUILDING IN CENTRAL KALIMANTAN - Gunawan, I Gede Dharman; Pranata, Pranata; Astawa, I Nyoman Sidi; Suda, I Ketut; Indiani, Ni Made (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
This paper discusses the establishment of the implementation of tolerance education at different religious places of worship in one place. The existence of places of worship of different religions side by side throughout Indonesia is still not much. In addition to the Mandala Puja worship complex in Bali where there are mosques, churches, temples, and vihara, there is also one of the places of worship of different religions in Tumbang Kalang Village, Antang Kalang District, East Kotawaringin Regency, Central Kalimantan. The government continues to foster a harmonious relationship between religious communities so that this area can be an example and a barometer of religious harmony in Central Kalimantan. There are four houses of worship at once, namely mosques, Catholic churches, Protestant churches and Balai Basarah for Kaharingan Hindus. The purpose of implementing tolerance education is to strengthen community togetherness and harmony regardless of ethnic and religious differences. Although worship is according to their respective religions, but after worship it is hoped that a family atmosphere will always be created and for the development of peace. With houses of worship in the same location, the community will often meet so that the relationship of kinship and harmony between religious groups is getting stronger. Differences in tribes, religions, races and intergroups do not make the community divided, it must be a unifying society for peace building.